How can interventions that target forest-goers be tailored to accelerate malaria elimination in the Greater Mekong Subregion? A systematic review of the qualitative literature - Nofal, S; Peto, T; Adhikari, B; Tripura, R; Callery, J; Bui, T; Von Seidlein, L; Pell, C (BioMed Central, 2019)
Background Despite decreases in incidence and related mortality, malaria remains a major public health challenge in the Greater Mekong Sub-region (GMS). The emergence of artemisinin resistance threatens these gains and has prompted efforts to accelerate elimination in the region. In the GMS, transmission now clusters in hotspots along international borders and among high-risk populations, including forest-goers. To eliminate malaria in the region, interventions must target such hard-to-reach populations. This review provides a comprehensive overview of the qualitative research on behaviours and perceptions that influence uptake of and adherence to malaria interventions among forest-goers in the GMS. Methods A systematic search strategy was used to identify relevant sources, including database (OVID SP, PubMed, ISI Web of Knowledge) and bibliographic searches. Relevant findings from qualitative research methods were extracted and thematic analysis undertaken. Results Of 268 sources retrieved in searches twenty-two were reviewed. Most reported studies were conducted in Cambodia (n = 10), and were published after 2014 (n = 16). Four major themes emerged that are particularly relevant to the design of intervention packages targeted at forest-goers: (1) understanding of malaria and perceived risk; (2) preventive measures used when visiting the forest; (3) behaviours that put forest-goers at risk of infection; and, (4) malaria-related treatment seeking. There were notable differences across the reviewed articles that suggest the need for a locally tailored approach. Conclusion A more detailed characterization of forest activities is needed but research on this topic raises methodological challenges. Current vector control measures have limitations, with use of insecticidal-treated nets, hammocks and repellents influenced by the type of forest activities and the characteristics of these measures. In contrast, anti-malarial drugs, for example, as chemoprophylaxis, hold promise but require further evaluation.